Processing and Interconnections of Finely Segmented Semiconductor Pixel Detectors for Applications in Particle Physics and Photon Detection - Härkönen, J.; Ott, J.; Gädda, A.; Bezak, M.; Brücken, E.; Tuovinen, E.; Bharthuar, S.; Luukka, P.; Tuominen, E. (Frontiers in Physics, 2021)
Radiation hardness is in the focus of the development of particle tracking and photon imaging detector installations. Semiconductor detectors, widely used in High-Energy Physics (HEP) experiments, have turned into capacitive-coupled (AC-coupled) detectors from the originally developed conductively coupled (DC-coupled) detectors. This is due to the superior isolation of radiation induced leakage current in AC-coupled detectors. However, some modern detector systems such as the tracking detectors in the CERN LHC CMS or ATLAS experiments are still DC-coupled. This originates from the difficult implementation of the AC-coupling on very small pixel detector areas. In this report, we describe our advances in the detector processing technology. The first topic is the applications of Atomic Layer Deposition (ALD) processing technology, which enables very high densities of capacitance and resistance that are needed when the dimensions of the physical segmentation of pixel detectors need to be scaled down. The second topic is Flip-Chip/bump-bonding interconnection technology which is necessary in order to manufacture pixel detector modules in large scale with more than >99% yield of noise-free and faultless pixels and detector channels.